Co-precipitation method for preparation of Bi3TiNbO9 powders - Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Patil, S. D.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure, ultrafine, single phase Bi3TiNbO9 (BTN). An aqueous ammonium hydroxide solution was used to simultaneously precipitate Bi3+, Ti4+ and Nb5+, cations as hydroxides under basic conditions (pH similar to 9). No pyrochlore phase was found while heating powder at 500 degrees C and pure BTN phase was found to be formed by X-ray diffraction (XRD). For comparison, BTN samples were also synthesized by the traditional solid state method. The sequence of phase formation in both cases were investigated by XRD studies. (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; Oxides; XRD

Co-precipitation technique to prepare BiNbO4 powders - Radha, R.; Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique was successfully used for the preparation of pure ultrafine single phase BiNbO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. For comparison, BN powders were also prepared by the traditional solid-state method. It is observed that the co-precipitation technique produces BiNbO4 on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the solid-state method. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Co-precipitation technique to prepare BiTaO4 powders - Muthurajan, H.; Gupta, U. N.; Rituraj, B.; Rao, N. Koteswara; Pradhan, Sivaram; Radha, R.; Ravi, V. (Materials Letters, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure ultrafine single phase BiTaO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. This precursor, on heating at 600 degrees C, produced product phase. This is the lowest temperature for the formation of BiTaO4 phase so far reported in the literature. For comparison BiTaO4 powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: BiTaO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis and characterization of BiNbO4 powders - Radha, R.; Muthurajan, H.; Rao, N. Koteswara; Pradhan, Sivaram; Gupta, U. N.; Jha, Ratnesh Kumar; Mirji, S. A.; Ravi, V. (Materials Characterization, 2008)
BiNbO4 powders, a potential microwave dielectric ceramic were prepared by both coprecipitation and solid state techniques. In the former method, an aqueous ammonium hydroxide was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. It is observed that the co-precipitation produces BiNbO4 phase on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the case of solid state method. The phase contents and lattice parameters were studied by powder X-ray diffraction. The sequence of the reaction and phase evolution of BiNbO4 were also studied by the X-ray diffraction. The samples were characterized by the differential-thermal/thermo-gravimetric analyses and scanning electron microscopy techniques. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis of SrNb2O6 and SrTa2O6 using hydroxide precursor - Muthurajan, H.; Kumar, H. H.; Koteswara Rao, N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Ravi, V. (Materials Letters, 2008)
SrNb2O6 (SN) or SrTA(2)O(6) (ST) compounds were prepared at low temperatures for the first time from hydroxide precursors. A simple procedure of mixing commercially purchased strontium hydroxide and niobium (or tantalum) hydroxide thoroughly together and heating at a low temperature (<400 degrees C) produced SrNb2O6 (SN) or SrTa2O6 (ST) powders. This is the lowest temperature so far reported for the formation of these phases. These materials are potential candidates for ferroelectric and electro-optic applications. The reaction sequence and evolution of the phase formation were investigated by X-ray diffraction (XRD) studies. The average particle size and morphology of these powders were studied by scanning electron microscopy (SEM). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction

Novel hydroxide precursors for low temperature synthesis of selected ternary oxides - Muthurajan, H.; Rao, N. Koteswara; Gupta, U. N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Kumar, H. H.; Mirji, S. A.; Ravi, V. (Materials Research Bulletin, 2008)
A novel method of using hydroxide precursors to reduce the synthesis temperature for few selected ternary oxides has been presented here. This technique is very useful and advantageous when the ternary oxides contain an alkaline earth element. The selected compositions for this method are BaCeO3 (BC), BaBiO3 (BB), La0.7Sr0.3CoO3 (LSCO) and BaBi2Nb2O9 (BBN). Commercially purchased strontium (or barium) hydroxide and freshly prepared lanthanum, cobalt, bismuth and niobium hydroxides were mixed thoroughly in stoichiometric ratio and heated at different temperatures ranging from 100 to 700 degrees C for 10 h for corresponding compositions. The sequence of the reaction and evolution of the product phase were studied by the X-ray diffraction (XRD) studies. The phase purity and lattice parameters were also determined by XRD investigations. All the product phases in each case were formed at relatively low temperature than when they were prepared by co-precipitation or solid state method. The morphology and average particle size of these powders were investigated by scanning electron microscopy (SEM). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Novel hydroxide precursors to prepare NaNbO3 and KNbO3 - Muthurajan, H.; Kumar, H. H.; Samuel, V.; Gupta, U. N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh niobium, hydroxide was precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing potassium (or sodium) and niobium hydroxides together and heating at a low temperature (<400 degrees C) produced KNbO3 (KN) or NaNbO3 (NN) powders. This is the lowest temperature so far reported for the formation of these phases. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by scanning electron microscopy (SEM). (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; niobates; Perovskites; powders; X-ray methods

Novel technique to prepare LiTaO3 at low temperature - Muthurajan, H.; Kumar, H. H.; Natarajan, N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh tantalum hydroxide was precipitated from TaF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and tantalum hydroxides together and heating at a low temperature (450 degrees C) produced pure ultrafine single phase LiTaO3 (LT). This is the lowest temperature so far reported for the formation of LT in the literature. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical synthesis X-ray diffraction; Electron microscopy; electronic materials; LiTaO3

Synthesis of LSMO at low temperature by novel hydroxide precursor technique - Gupta, U. N.; Muthurajan, H.; Kumar, H. H.; Rao, N. Koteswara; Gokhale, Suresh P.; Ravi, V. (Materials Letters, 2008)
A novel technique of mixing individual hydroxide is employed to prepare La0.65Sr0.35MnO3 (LSMO) at low temperature. Freshly prepared lanthanum and manganese hydroxides are mixed thoroughly with strontium hydroxide in stoichiometric ratio and heated at different temperatures ranging from 100 to 500 degrees C for 6 h. At 500 degrees C, formation of La0.65Sr0.35MnO3 was confirmed by the X-ray diffraction studies (XRD). This is the lowest temperature so far reported in the literature. The particle size and morphology were investigated by scanning electron microscopy (SEM). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; La0.65Sr0.35MnO3; Oxides; Precipitation; X-ray diffraction